2018
DOI: 10.1111/trf.14874
|View full text |Cite
|
Sign up to set email alerts
|

Online responses to motivational interview questions enhance blood donation intention

Abstract: BACKGROUND A motivational interview may promote blood donor retention, but live interviews can be costly. To address this challenge, we conducted two studies to examine the impact of online delivery of motivational interview content on donation intention. STUDY DESIGN AND METHODS In Study 1, a total of 3883 respondents (52.2% female; mean ± SD age, 35.69 ± 11.3 years) completed a donation commitment measure and were randomly assigned to one of seven motivational interview–based questions or a no‐question contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…Thus, one simple step to enhance completion may be to reduce the number of questions asked. Indeed, we recently demonstrated that it is possible to promote donation intention using as few as one to three motivational interview questions . On a deeper level, the automated interview is currently technically limited in terms of the degree to which it can be conducted in a manner consistent with the process and spirit of motivational interviewing .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one simple step to enhance completion may be to reduce the number of questions asked. Indeed, we recently demonstrated that it is possible to promote donation intention using as few as one to three motivational interview questions . On a deeper level, the automated interview is currently technically limited in terms of the degree to which it can be conducted in a manner consistent with the process and spirit of motivational interviewing .…”
Section: Discussionmentioning
confidence: 99%
“…For both studies, participants enrolled using Amazon's Mechanical Turk, an online marketplace where participants complete small tasks (eg, surveys) for monetary compensation. This method has been used previously in blood donor motivation research 8,[16][17][18] and has been shown to be a timeefficient method to gather reliable and valid data, 19 particularly when the design includes items to screen for attention and consistency of responses. 20 In the present studies, participants were only able to view and respond to the survey if their computer had an IP address located within the United States.…”
Section: Recruitmentmentioning
confidence: 99%
“…7 In another set of studies, individuals moderately committed to donating blood reported higher donation intention after answering one or more motivational interview questions relative to not answering any questions. 8 These questions included asking individuals to reflect on (a) how they would feel if they did or did not donate blood; (b) the best or worst thing that could happen if they did or did not donate blood, respectively; (c) how donating blood aligned with their values; and/or (d) their confidence in being able to donate blood. The research reported herein entails further study of these motivational questions.…”
mentioning
confidence: 99%
See 2 more Smart Citations